The Effectiveness of Holographic Learning Media on The Learning Outcomes of Class V IPAS Material of The Earth’s Layers - Yusuf Nur Abidin; Sigit Yulianto (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The use of inappropriate learning media often causes the problem of unsatisfactory learning outcomes in students. Therefore, researchers are interested in examining the utilization of hologram learning media to increase students' interest in learning and directly lift the quality of their learning outcomes. This study aims to evaluate the effectiveness of using hologram learning media in improving the achievement of learning outcomes in Natural and Social Sciences (NSP) subjects for fifth-grade students at Wonosari 01 Elementary School in Semarang City. Using a quasi-experimental Pretest-Posttest Control Group design, 51 students were sampled and divided into experimental class VA (25 students) and control class VB (26 students). The results showed a significant effect of hologram learning media on student learning outcomes. Hypothesis analysis using a t-test showed that the t(calculated) value of 41.37 exceeded the t(table) value of 2.009 at the significance level of ????= 0.05. This shows that the use of hologram learning media statistically significantly affects the learning outcomes of fifth-grade students at Wonosari 01 Elementary School in Semarang City.